Kosovo kot mednarodni problem - Bebler, Anton (Teorija in praksa, 2011)
Conquered by Serbia in 1912, Kosovo became a controversial international problem in 1997, six years after the breakdown of the SFR of Yugoslavia. Unique in some respects, Kosovo's case is also similar to many other politicalconflicts within multinational states related to ethnic, cultural andreligious divides. De facto separated from Serbia by a NATO "humanitarian intervention" in 1999, in 2008 Kosovo became an example of a successful "remedial secession", arguably concluding Yugoslavia's dissolution into seven independent states. Yet Kosovo's declaration of independence divided the international community as well as EU and NATO members. The ICJ's advisory opinion, although favourable to Kosovo's cause, did not legalise all secessions. In order to solidify peace and stability in the Western Balkans, the international community will for quite some time have to remain attentive to and actively involved in assisting this youngest European state and in helping Kosovo and Serbia normalise their relations
Keywords: International courts; Mednarodna sodišča; Neodvisnost; Confederation of New Trade Unions of Slovenia "Independence"; Independence; Kosovo; Serbia; Srbija; politična zgodovina; politični konflikti